- #1
mathmari
Gold Member
MHB
- 5,049
- 7
Hey!
I am looking for an example of an application of the double induction.
For that I tried to show that the addition is commutative: For $m,n\in \mathbb{N}$ it holds that $m+n=n+m$. I have done the following:
For each $n\in \mathbb{N}$ let $E_n$ be the proposition: $\forall m\in \mathbb{N}: m+n=n+m$.
Base Case:
For $n = 1$ we want to show that $\forall m\in \mathbb{N}: m+1=1+m$
We suppose that the proposition holds for a specific $n\in \mathbb{N}$, i.e. let $\forall m\in \mathbb{N}: m+n=n+m$ (I.H.2) Inductive Step:
We want to show that the proposition holds also for $n+1$, so $\forall m\in \mathbb{N}: m+(n+1)=(n+1)+m$.
I am looking for an example of an application of the double induction.
For that I tried to show that the addition is commutative: For $m,n\in \mathbb{N}$ it holds that $m+n=n+m$. I have done the following:
For each $n\in \mathbb{N}$ let $E_n$ be the proposition: $\forall m\in \mathbb{N}: m+n=n+m$.
Base Case:
For $n = 1$ we want to show that $\forall m\in \mathbb{N}: m+1=1+m$
- Base Case: For $m=1$ the left side is equal to $1+1=2$ and the right side is the same.
- Inductive Hypothesis: Let the proposition hold for a specific $m\in \mathbb{N}$, i.e. let$m+1=1+m$ (I.H.1)
- Inductive Step: We want to show that the proposition holds also for $m+1$, so $(m+1)+1=1+(m+1)$.
We have the following:
\begin{equation*}(m+1)+1 \overset{\text{ (I.H.1) }}{ = } (1+m)+1=1+m+1=1+(m+1)\end{equation*}
Therefore the proposition holds for $m + 1$.
We suppose that the proposition holds for a specific $n\in \mathbb{N}$, i.e. let $\forall m\in \mathbb{N}: m+n=n+m$ (I.H.2) Inductive Step:
We want to show that the proposition holds also for $n+1$, so $\forall m\in \mathbb{N}: m+(n+1)=(n+1)+m$.
- Base Case: For $m=1$ the left side is equal to $1+(n+1)=1+n+1=(1+n)+1\overset{\text{ (I.H.2) }}{ = }(n+1)+1=n+1+1=n+2$ and the right side is equal to $(n+1)+1=n+1+1=n+2$.
- Inductive Hypothesis: We suppose that the proposition holds for a specific $m\in \mathbb{N}$, i.e. let $m+(n+1)=(n+1)+m$ (I.H.3)
- Inductive Step: We want to show that the proposition holds also for $m+1$, so $(m+1)+(n+1)=(n+1)+(m+1)$.
We have the following:
\begin{align*}(m+1)+(n+1)&=m+1+n+1 \\ & =m+(1+n)+1 \\ & \overset{\text{ (I.B.2) }}{ = }m+(n+1)+1 \\ & =m+n+1+1 \\ & =m+(n+1)+1 \\ & \overset{\text{ (I.B.3) }}{ = }(n+1)+m+1 \\ & =(n+1)+(m+1)\end{align*}
Therefore the proposition holds for $m + 1$.